Association of plasma YKL‐40 with brain amyloidosis, memory performance, and sex in subjective memory complainers: Biomarkers (non‐neuroimaging) / plasma/serum/urine biomarkers. (7th December 2020) - Baldacci, Filippo; Lemercier, Pablo; Vergallo, Andrea; Chiesa, Patrizia Andrea; Zetterberg, Henrik; Blennow, Kaj; Potier, Marie‐Claude; Habert, Marie‐Odile; Cavedo, Enrica; Caraci, Filippo; Dubois, Bruno; Lista, Simone; et al.
Abstract: Background: Neuroinflammation – a crucial early pathomechanistic alteration of Alzheimer's disease (AD) – may represent either a detrimental or a compensatory mechanism or both, based on the disease stage. YKL‐40, a glycoprotein highly expressed in human glia cells, is a candidate biomarker to in vivo track glial‐related neuroinflammation in AD. Few studies explored, in cognitively healthy individuals, the potential influence of key biological factors – age, sex, Apolipoprotein E ( APOE ) ε4 allele – on YKL‐40 plasma concentrations as well as its association with other AD pathophysiological mechanisms and cognitive scores. Method: We assessed the cross‐sectional and longitudinal impact of relevant biological factors – sex, age, APOE ε4 allele – on YKL‐40. Moreover, we explored the cross‐sectional and longitudinal association of YKL‐40 with: 1) global/regional brain amyloid beta (Aβ) deposition using Aβ‐positron emission tomography (PET) imaging; 2) synaptic loss, using [ 18 F]‐fluorodeoxyglucose‐PET ([ 18 F]‐FDG‐PET); 3) neurodegeneration using magnetic resonance imaging (MRI), i.e. hippocampal, entorhinal cortex, and basal forebrain volumes. We also sought for the potential association between YKL‐40 and the degree of cognitive performance. The study was performed in the INSIGHT‐preAD cohort (N=314, M=114, F=200, aged 70 to 85), a large observational monocentric French academic cohort (Pitié‐Salpêtrière University Hospital, Paris) of individuals with subjective memory complaints (SMC), a condition at risk for AD. We used mixed models with interaction of YKL‐40 with time. Result: Men displayed higher YKL‐40 concentrations than women at each time point investigated (b=0.171, t=2.434, P =0.015). YKL‐40 presented an age‐associated increase at each time point investigated (b=0.029, t=3.004, P =0.003). YKL‐40 was negatively associated with baseline Aβ deposition, at both global (b=‐0.025, t=‐1.992, P =0.047) and regional level. Besides, one‐year increase of YKL‐40 concentration was positively associated with memory performance, longitudinally (b=0.308, z=2.280, P =0.023). YKL‐40 showed no effect on synaptic loss or neurodegeneration. Conclusion: Plasma YKL‐40 concentrations present an age‐associated increase with men showing higher levels than women, irrespective of the time point, thus indicating a potential sexual dimorphism in neuroinflammation. Moreover, the association of higher YKL‐40 concentrations with lower overall/regional cross‐sectional Aβ deposition and higher memory scores over time indicates a non‐clinical detrimental/potential protective effect of glia activation on incipient brain amyloidosis and synaptic network homeostasis.